2021
DOI: 10.1016/s2468-1253(21)00077-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatitis C treatment-as-prevention within Australian prisons (SToP-C): a prospective cohort study

Abstract: Background: Limited empirical evidence exists for hepatitis C virus (HCV) treatment-asprevention. The Surveillance and Treatment of Prisoners with hepatitis C (SToP-C) study assessed HCV treatment-as-prevention in four Australian prisons.Methods: SToP-C is a non-randomised trial, including a pre/post analysis within a prospective longitudinal cohort of people incarcerated in two maximum-(male) and two medium-security prisons (one male, one female). All prison inmates at least 18 years were eligible for enrolme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…Still, for vulnerable groups with low compliance, short duration treatment may be justified. Several studies in prison settings have shown this to be an effective way to scale up treatment for chronic hepatitis C [ 40 ], but prisoners with short sentences may not be offered treatment and for hospitalized patients, including psychiatric wards, the treatment duration will also be a critical factor for success.…”
Section: Discussionmentioning
confidence: 99%
“…Still, for vulnerable groups with low compliance, short duration treatment may be justified. Several studies in prison settings have shown this to be an effective way to scale up treatment for chronic hepatitis C [ 40 ], but prisoners with short sentences may not be offered treatment and for hospitalized patients, including psychiatric wards, the treatment duration will also be a critical factor for success.…”
Section: Discussionmentioning
confidence: 99%
“…HCV therapy has been revolutionized in the last decade due to the development of safe and effective DAAs. Moreover, the scale up of prompt HCV infection diagnosis and universal DAA treatment in high-risk settings has recently demonstrated the potential for improved infection control with a "treatment as prevention" strategy [141,142]. To enhance HCV elimination efforts, the next frontier in HCV research is the development and implementation of accessible preventative strategies (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Effective approaches to increasing testing for HCV and scaling up of treatment with DAAs can also be used as ‘treatment as prevention’. This approach was practiced in an Australian prison population and led to a significant reduction in incidence of new HCV infections[ 80 ].…”
Section: Hepatitis C Virusmentioning
confidence: 99%